Permanent record - Snowden, Edward J., 1983- (New York : Metropolitan Books, Henry Holt and Company, 2019)
"In 2013, twenty-nine-year-old Edward Snowden shocked the world when he broke with the American intelligence establishment and revealed that the United States government was secretly pursuing the means to collect every single phone call, text message, and email. The result would be an unprecedented system of mass surveillance with the ability to pry into the private lives of every person on earth. Six years later, Snowden reveals for the very first time how he helped to build this system and why he was moved to expose it."-- Book jacket.
Part one. Looking through the window -- The invisible wall -- Beltway boy -- American online -- Hacking -- Incomplete -- 9/11 -- 9/12 -- X-rays -- Cleared and in love. Part two. The system -- Homo contractus -- Indoc -- The count of the hill -- Geneva -- Tokyo -- Home on the cloud -- On the couch. Part three. The tunnel -- Heartbeat -- Whistleblowing -- Fourth estate -- Read, write, execute -- Encrypt -- The boy -- Hong Kong -- Moscow -- From the diaries of Lindsey Mills -- Love and exile.
Keywords: Snowden, Edward J., -- 1983-; United States. -- National Security Agency -- Officials and employees -- Biography; Government information -- United States; Whistle blowing -- United States; Leaks (Disclosure of information) -- United States; Autobiographies